Anxiety, depression, and HRQoL in pediatric microtia patients following ear reconstruction: a cross-sectional study - Liu, Xinyi; Huang, Ying; Yang, Lin; Zhang, Enming; Yang, Jiafei; Meng, Liujing; Ma, Liping; Fu, Zhengzhen; Zhou, Yanchun; Bian, Weiwei (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of this study was to evaluate the levels of anxiety, depression, and health-related quality of life (HRQoL) in patients with congenital microtia after ear recontruction surgery and identify influencing factors of HRQoL.MethodA cross-sectional study was conducted in 152 patients with congenital microtia (aged 8–18 years) who underwent ear reconstruction at a tertiary hospital in Shanghai from April 2023 to September 2024. The assessment tools, including the Hospital Anxiety and Depression Scale, and the Pediatric Quality of Life Inventory Version 4.0 Generic Core Scales, were used to assess symptoms of anxiety, symptoms of depression and HRQoL within 24 hours postoperatively. Multiple linear regression was performed to explore the factors affecting HRQoL.ResultsPostoperatively, 21.7% of patients with congenital microtia reported symptoms of anxiety, and 17.8% reported symptoms of depression. Patients with congenital microtia have significantly lower HRQoL scores than the healthy norm group. Anxiety and depression showed moderate negative correlations with HRQoL score (r = -0.433 and -0.486, respectively, p < 0.001). Multivariate analysis showed that residence (95% CI: -6.661, -0.902, p = 0.010), surgery type (95% CI: 2.113, 9.496, p = 0.002), pain score (95% CI: -1.836, -0.031, p = 0.043) and depression score (95% CI: -1.644, -0.318, p = 0.004) were significantly associated with HRQoL in patients with congenital microtia after surgery.ConclusionPatients with congenital microtia experience significant psychological distress and reduced quality of life after ear reconstruction surgery, with anxiety, depression, pain, and socio-demographic factors playing critical roles. These findings underscore the necessity of an integrated care model that incorporates psychological evaluation, pain management, and personalized support to improve mental health and quality of life in these patients.